Antioxidant properties of extracts from the above-ground parts of Filipendula ulmaria; Pharmaceutical Chemistry Journal; Vol. 40, iss. 12 - Shilova I. V.; Krasnov E. A.; Korotkova E. I. Elena Ivanovna; Nagaev M. G.; Lukina A. N. (2006, 2006)
Title screen